Analysis of Public Service Quality on Community Satisfaction at the Sukahati Village Office, Citeureup District, Bogor Regency - Refani Monica Gusela; Benny Osta Nababan; Septa Riadi (Majalah Ilmiah Bijak, 2021)
This study aims to determine the level of quality of public services at the Sukahati Citeureup Village Office, then to determine the level of satisfaction at the Sukahati Citeureup Village Office and to determine the elements that must be improved so that community satisfaction can be fulfilled. The research method used in this research is descriptive quantitative research. Data collection techniques were carried out by surveys and questionnaires. The results showed that all service quality attributes got agap negative. Then for the value of the community satisfaction index at the Sukahati Citeureup Village Office, it is currently found to be 74.03% which means that the community is quite satisfied but it is not considered optimal as a whole, and in the Importance Performance Analysis (IPA), there are two service attributes that must be prioritized. The main thing to be repaired by the Sukahati Citeureup Village Office is to meet community satisfaction.This study aims to determine the level of quality of public services at the Sukahati Citeureup Village Office, then to determine the level of satisfaction at the Sukahati Citeureup Village Office and to determine the elements that must be improved so that community satisfaction can be fulfilled. The research method used in this research is descriptive quantitative research. Data collection techniques were carried out by surveys and questionnaires. The results showed that all service quality attributes got agap negative. Then for the value of the community satisfaction index at the Sukahati Citeureup Village Office, it is currently found to be 74.03% which means that the community is quite satisfied but it is not considered optimal as a whole, and in the Importance Performance Analysis (IPA), there are two service attributes that must be prioritized. The main thing to be repaired by the Sukahati Citeureup Village Office is to meet community satisfaction.